Digital Mission in a Post-Pandemic World: Reimagining Evangelism and Doscipleship - Kezia Meifa Supit; Michelle Johannis; Jeane Maisudu; Jeshinta Tarek (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
The COVID-19 pandemic marked a significant turning point in the global church's approachto mission and ministry, particularly through the adoption of digital spaces. The rapid shift to digitalplatforms was not merely a practical adaptation but reflected a deeper transformation in how thechurch understands presence, community, and engagement in the world. This article aims to examinehow evangelism and discipleship practices have evolved in digital forms in the post-pandemic context,and to explore the theological and ethical implications of "digital presence" within contemporarymissiology. Using a practical theology approach, this study employs literature analysis, theologicalreflection, and case studies from digital church practices as its primary methods. The main findingsreveal that evangelism has shifted towards creative digital content targeting digital-native generations,while discipleship is increasingly practiced through online communities and digital spirituality. At thesame time, the study identifies key issues such as the validity of digital sacraments, the risk of faithcommodification, and the challenge of fostering authentic relationships in virtual spaces. This articlesynthesizes the idea that digital mission represents a new form of incarnational ministry in the digitalage, calling for a hybrid ecclesiology that integrates both physical and digital presence. In conclusion,digital mission is not simply a crisis response to the pandemic but a long-term theological and strategictransformation in how the church participates as the Body of Christ in a digitally connected world.